Keterampilan Komunikasi Siswa Kelas V SDN 101835 Sibolangit di dalam Proses Pembelajaran - Bukit, Servista (Yayasan Pendidikan Internasional Bengkulu, 2022)
Communication skills are very important to be mastered by each student so that they can express opinions, ask teachers and friends and can exchange information with teachers and friends in the learning process. Communication skills can be trained to make children brave in speaking to anyone in the learning process. So that students can use communication as a source of information for them in mastering learning material. This study focuses on analyzing the communication skills of fifth grade students at SDN 101835 Sibolangit in the learning process. The results of this analysis become a preliminary study for teachers to see the learning needs of students. This study shows that students' communication skills are still categorized as unskilled with a percentage of 41.20%. Thus it still takes strong efforts from teachers to improve students' communication skills in learning. Efforts that can be made such as applying the debate learning model, applying the role playing model in learning and using simulation methods in learning. The results of this study became the initial strength in the research process to determine the right strategy to improve the quality of learning.